Development Of A Numerical Model For The Simulation Of Mudflow Phenomenon - Alexander, Yeo Ming Ming (Universiti Sains Malaysia, 2017)
Recently, mudflow has been happening on a more frequent basis due to the rapid development especially in the mountainous and highland areas. Mudflow is known to have devastating impacts on lives and properties. One of the most probable causes of mudflow is deforestation. Mudflow is hard to be predicted but mitigation plans can be developed to reduce the negative impacts of mudflow. Numerical modelling can be a handy tool to predict the dynamics and flow extent of a mudflow disaster and therefore it can be very useful and indispensable tool to develop a sound mitigation plan. In this work, a higher order numerical scheme known as the cubic interpolation profile (CIP) was adopted in the numerical model. Like other numerical models, this numerical model was verified with analytical solution, numerical solution and experimental results obtained by past researchers. The numerical model was used to simulate mudflow scenarios after ensuring that the performance of the numerical model was satisfactory through the close agreement between the results produced by the numerical model and the data obtained from literature in the verification process. The model can be extended for practical use by incorporating geospatial data in the near future.